Indy dreams and urban nightmares: speed merchants, spectacle, and the struggle over public space in the world-class city - Lowes, Mark Douglas, 1969- (Toronto, Ont. : University of Toronto Press, 2002)
Lowes examines the conflict that arose between a Vancouver community and the civic boosters who wanted to move the Molson Indy Vancouver motorsport event to their neighbourhood park.
Includes bibliographical references (p. [141]-146) and index.
JSTOR
Keywords: Community organization -- Citizen participation -- Case studies; Urban economics -- Case studies; Sports and tourism -- British Columbia -- Vancouver; Automobile racing -- British Columbia -- Vancouver; Public spaces -- British Columbia -- Vancouver; City planning -- British Columbia -- Vancouver -- Citizen participation; Hastings Park (Vancouver, B.C.); City planning -- Citizen participation; Automobile racing -- British Columbia -- Vancouver; City planning -- British Columbia -- Vancouver -- Citizen participation; Community organization -- Citizen participation -- Case studies; Electronic books; Hastings Park (Vancouver, B.C.).; Public spaces -- British Columbia -- Vancouver; Sports and tourism -- British Columbia -- Vancouver; Urban economics -- Case studies; Courses automobiles -- Colombie-Britannique -- Vancouver; Urbanisme -- Colombie-Britannique -- Vancouver -- Participation des citoyens; Espaces publics -- Colombie-Britannique -- Vancouver; Économie urbaine -- Études de cas; Sports et tourisme -- Colombie-Britannique -- Vancouver; Organisation communautaire -- Participation des citoyens -- Études de cas; Hastings Park (Vancouver, C.-B.); Urbanisme participatif; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development; Automobile racing; City planning -- Citizen participation; Community organization -- Citizen participation; Public spaces; Sports and tourism; Urban economics; British Columbia -- Vancouver; British Columbia -- Vancouver -- Hastings Park; Case studies